2003
DOI: 10.1046/j.1432-1033.2003.03591.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐operation of domain‐binding and calcium‐binding sites in the activation of gelsolin

Abstract: Gelsolin is an abundant calcium dependent actin filament severing and capping protein. In the absence of calcium the molecule is compact but in the presence of calcium, as its six similar domains alter their relative position, a generally more open configuration is adopted to reveal the three actin binding sites. It is generally held that a Ôhelical-latchÕ at the C-terminus of gelsolin's domain 6 (G6), binds domain 2 (G2) to keep gelsolin in the calcium-free compact state, and that the crutial calcium binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…As an extension of this, some HALF proteins have also been identified where the metal ion and nucleotide binding sites are only partly formed by the HALF partner. Formation of the complete binding site thus requires additional residues presented on the surface of a different protein; examples include the actin‐gelsolin complex and glycerol kinase 53, 54. Analysis of the YeaZ crystal lattice packing suggests a “crescent”‐shaped dimer, an unusual arrangement for a HALF protein.…”
Section: Resultsmentioning
confidence: 99%
“…As an extension of this, some HALF proteins have also been identified where the metal ion and nucleotide binding sites are only partly formed by the HALF partner. Formation of the complete binding site thus requires additional residues presented on the surface of a different protein; examples include the actin‐gelsolin complex and glycerol kinase 53, 54. Analysis of the YeaZ crystal lattice packing suggests a “crescent”‐shaped dimer, an unusual arrangement for a HALF protein.…”
Section: Resultsmentioning
confidence: 99%
“…Inactive gelsolin undergoes either two or three conformational changes as calcium concentrations rise from 10 nM to ∼5 μM, as a result of binding of two or three calcium ions with K d values estimated to be 0.1 and/or 0.3 μM and 6.4 μM [Kinosian et al, ; Lin et al, ]. These events may reflect the release of the tail latch [Kwiatkowski et al, ; Pope et al, ; Kinosian et al, ; Lin et al, ; Lueck et al, ; Choe et al, ; Kolappan et al, ; Lagarrigue et al, ,b], for which recent evidence [Nag et al, ] implicates a cooperative pair of calcium‐binding events at the type‐2 sites in G2 and G6. Indeed, sequence analysis reveals that human gelsolin superfamily proteins that lack a full complement of six type‐2 sites still retain a type‐2 site in domain 2 (supervillin) or domain 6 (flightless I), testifying to the importance of breaking the domain 2:domain 6 interactions during activation (Fig.…”
Section: The Role Of Calcium In Activationmentioning
confidence: 99%
“…In addition to the above mentioned regulation of gelsolin activity by Ca 2ϩ ions and PIP2, acidic pH (ϳ6) has also been shown to enable actin assembly/disassembly function of gelsolin (12)(13)(14). It was shown that even when intracellular Ca 2ϩ concentrations were about subnanomolar range, pH value close to 6 allowed gelsolin/G-actin binding as estimated by an increase in fluorescence intensity of labeled actin, with the rate of formation of the complex being about five times faster at pH 6 than that at pH 8 (12).…”
mentioning
confidence: 99%